Shall we blog? profiling journalists in the blogsphere - Cena, Franco Emman Von M.
"This study seeks to find out how blogs or online journals are used by selected media practitioners and looks into how the blogging phenomenon started among journalists and how can it affect the practice of journalism in the country. To attain these objectives, this qualitative study employed the uses and gratifications theory as its major framework. The agenda-setting, self-discourse and information society theories of mass communication were also utilized. These theories will help explain how blogs are used by the journalist-bloggers. The researchers conducted 13 focused interviews of the following media practitioners: Ellen Tordesillas, Ederic Eder, Max Limpag, Nina Corpuz, John Nery, Ricky Carandang, RG Cruz, Bernadette Sembrano, Adrian Ayalin, Glenn Omanio, Howie Severino, Professor Danilo Arao, and Alecks Pabico. Based on the multiple case study or profiling done, this study found that blogs are considered to be an extension of the journalists' work and complement their jobs. The results also show that these bloggers believe that blogging goes not challenge or pose a threat to the practice of journalism in the country. Yet, they believe that it eventually will. The study also proved that blogs have become an alternative source of news and information, as well as analysis, commentary, and insight, even to the traditional media. Likewise, blogs have become a venue for their self-disclosure."